2006
DOI: 10.1079/pns2006495
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in genes of folate metabolism and neural-tube defect risk

Abstract: Neural-tube defects (NTD) are common congenital malformations that can lead to severe disability or even death. Periconceptional supplementation with the B-vitamin folic acid has been demonstrated to prevent 50-70% of NTD cases. Since the identification of the first genetic risk factor of NTD, the C677T single-nucleotide polymorphism (SNP) in the methylenetetrahydrofolate reductase (MTHFR) gene, and the observation that elevated plasma homocysteine levels are associated with NTD, research has focused on geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
1
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 113 publications
0
94
1
8
Order By: Relevance
“…The genes that encode the proteins/enzymes related to folate uptake and metabolism include many polymorphisms, among which MTHFR C677T, CBS 844ins68, GCPII H475Y, MTR A2756G, and MTRR A66G are known to affect folate and vitamin B12 intake (Uauy et al 2014). Genetic polymorphisms related to the folate pathway have been shown to be associated with functional implications and specific conditions including NTDs (van der Linden et al 2006), cardiovascular disease (Klerk et al 2002), and some types of cancers, such as colorectal, breast, and lung cancers (Lee 2009). To date, most studies have shown that the MTHFR C677T genotype is related to biomarkers, such as serum folate, tHcy concentration, and folate intake.…”
Section: Genetic Polymorphisms Related To Folate and Thcy Metabolism mentioning
confidence: 99%
“…The genes that encode the proteins/enzymes related to folate uptake and metabolism include many polymorphisms, among which MTHFR C677T, CBS 844ins68, GCPII H475Y, MTR A2756G, and MTRR A66G are known to affect folate and vitamin B12 intake (Uauy et al 2014). Genetic polymorphisms related to the folate pathway have been shown to be associated with functional implications and specific conditions including NTDs (van der Linden et al 2006), cardiovascular disease (Klerk et al 2002), and some types of cancers, such as colorectal, breast, and lung cancers (Lee 2009). To date, most studies have shown that the MTHFR C677T genotype is related to biomarkers, such as serum folate, tHcy concentration, and folate intake.…”
Section: Genetic Polymorphisms Related To Folate and Thcy Metabolism mentioning
confidence: 99%
“…The methionine synthase reductase (MTRR) 66A>G variant has emerged as a possible genetic risk factor for NTDs. Other potential candidates are the MTHFR 1298A>C, methylene-tetrahydrofolate dehydrogenase (MTHFD) 1958G>A and transcobalamin 776C>G variants 64 . Unfortunately, most single nucleotide polymorphisms (SNPs) tested have not been shown to be associated with NTD risks of substantial magnitude 64 .…”
Section: Other Candidate Genesmentioning
confidence: 99%
“…Other potential candidates are the MTHFR 1298A>C, methylene-tetrahydrofolate dehydrogenase (MTHFD) 1958G>A and transcobalamin 776C>G variants 64 . Unfortunately, most single nucleotide polymorphisms (SNPs) tested have not been shown to be associated with NTD risks of substantial magnitude 64 . This indicates that many of the candidate genes studied so far might not be important in the mechanisms underlying the link between folate and NTD risk.…”
Section: Other Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that nutrient deficiency is an important independent risk factor for birth defects (Zhang et al 2008a), and lower plasma concentrations of folate and vitamin B12 are related to an increased risk of NTDs in high-risk populations (Zhang et al 2009). Many polymorphisms in folate pathway genes have been investigated and shown to be associated with NTD risk (Zhu et al 2003;van der Linden et al 2006;Boyles et al 2006). However, none of the known folate pathway gene variants contribute substantially to the population burden of NTDs.…”
Section: Introductionmentioning
confidence: 99%